2011
DOI: 10.1002/cbic.201000639
|View full text |Cite
|
Sign up to set email alerts
|

Spacer Effects on in vivo Properties of DOTA‐Conjugated Dimeric [Tyr3]Octreotate Peptides Synthesized by a “CuI‐Click” and “Sulfo‐Click” Ligation Method

Abstract: We report on the SSTR2-binding properties of a series of four dimeric [Tyr3]octreotate analogues with different spacer lengths (nine, 19, 41, and 57 atoms) between the peptides. Two analogues (9 and 57 atoms) were selected as precursors for the design, synthesis, and biological evaluation of DOTA-conjugated dimeric [Tyr3]octreotate analogues for tumor targeting. These compounds were synthesized by using a two-stage click ligation procedure: a Cu(I) -catalyzed 1,3-dipolar cycloaddition ("copper-click" reaction)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…The alkyne derivative of DOTA-tris- tert -butyl ester was coupled to folate -γ-(4-azido)butane amide by similar chemistry 137. A versatile two stage click ligation method based on Cu I -catalyzed 1,3 dipolar addition and a thio acid/sulfonylazideamidation (“sulfo-click”) was developed for an efficient systhesis of dimeric peptide agents with various spacer lengths between the peptide units 138. A novel Cu-free click chemistry method has been developed for the conjugation of chelators functionalised with monofluorocyclooctyne to azide-modified peptide in aqueous solution at room temperature 139.…”
Section: Chemistry Of 68ga-based Imaging Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alkyne derivative of DOTA-tris- tert -butyl ester was coupled to folate -γ-(4-azido)butane amide by similar chemistry 137. A versatile two stage click ligation method based on Cu I -catalyzed 1,3 dipolar addition and a thio acid/sulfonylazideamidation (“sulfo-click”) was developed for an efficient systhesis of dimeric peptide agents with various spacer lengths between the peptide units 138. A novel Cu-free click chemistry method has been developed for the conjugation of chelators functionalised with monofluorocyclooctyne to azide-modified peptide in aqueous solution at room temperature 139.…”
Section: Chemistry Of 68ga-based Imaging Agentsmentioning
confidence: 99%
“…Fast tumour localization, blood clearance, and renal excretion are typical characteristics of clinically used [ 68 Ga]Ga-DOTA-TATE, [ 68 Ga]Ga-DOTA-TOC, [ 68 Ga]Ga-DOTA-1-Nal 3 -octreotide ([ 68 Ga]Ga-DOTA-NOC). Structure activity relation studies allowed fine tuning for the agent properties such as receptor affinity, in vivo stability, biodistribution, pharmacokinetics, excretion pathway, and kidney uptake, and pharmacological activity 138, 151-155.…”
Section: Imaging Of G-protein Coupled Receptor Familymentioning
confidence: 99%
“…Displacement assays showed that DOTA-TATE has a higher affinity for SSTR 2 than 800CW-TATE, however IC 50 values for both were in the nanomolar range. The lower affinity for 800CW-TATE may be due to steric hindrance, an altered configuration and/or electrical charge of the tracer [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The latter is either a radiometal chelator, which coordinates with a radiometal, or a suitable group for radio-halogenation, which is often connected with the pharmacophore through a linker (spacer) group. Linker groups are used ( Figure 1): (1) to increase the distance between the ligand and the chelator group and thus, minimize the interference of the radiolabeled domain with the binding pocket of the ligand in the receptor; (2) to enhance the interactions between the ligand and its binding pocket; (3) to enable the addition of a second or of multiple binding pharmacophore groups leading to multimeric ligands; (4) to increase the distance between the multiple pharmacophores in order to enable simultaneous binding on more than one receptors ( Figure 1a); (5) to change the pharmacokinetic properties of the radioligand, altering its hydrophobicity and eventually increase its apparent local concentration when it reaches the receptor's binding area [3][4][5]. Binding models for multimers on the cell surface: (a) The binding of a radioligand to a cell surface receptors and the multimeric approach resulting in simultaneous binding of two pharmacophores connected via a long linker with two receptors, (b) improved binding efficiency of a ligand, due to the increased apparent local concentration of the pharmacophore (statistical effect) in the micro-environment of the receptor; (c) basic principles for the design of monomeric and multimeric radioligands (where n = number of pharmacophores).…”
Section: Introduction 1multimeric Radioligandsmentioning
confidence: 99%